2015
DOI: 10.1104/pp.15.00134
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Blue Light Response Is Present in Early Vascular Plants

Abstract: Light is a major environmental factor required for stomatal opening. Blue light (BL) induces stomatal opening in higher plants as a signal under the photosynthetic active radiation. The stomatal BL response is not present in the fern species of Polypodiopsida. The acquisition of a stomatal BL response might provide competitive advantages in both the uptake of CO 2 and prevention of water loss with the ability to rapidly open and close stomata. We surveyed the stomatal opening in response to strong red light (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 49 publications
(97 reference statements)
7
78
0
Order By: Relevance
“…A wider study of stomatal ABA responsiveness across the evolutionary tree of ferns would be required to understand how guard cell ABA responsiveness has evolved. For example, an analysis of different fern classes showed that, whereas stomatal opening in response to blue light is present in lycophytes and most classes of ferns, it has been lost in the fern group Polypodiopsida (Doi et al, 2015). Thus, it is conceivable that the stomatal ABA responsiveness has been lost in some branches of the evolutionary tree of ferns, and systematic analysis of stomatal responses in different taxa is required to bring further insight to this question.…”
Section: Resultsmentioning
confidence: 99%
“…A wider study of stomatal ABA responsiveness across the evolutionary tree of ferns would be required to understand how guard cell ABA responsiveness has evolved. For example, an analysis of different fern classes showed that, whereas stomatal opening in response to blue light is present in lycophytes and most classes of ferns, it has been lost in the fern group Polypodiopsida (Doi et al, 2015). Thus, it is conceivable that the stomatal ABA responsiveness has been lost in some branches of the evolutionary tree of ferns, and systematic analysis of stomatal responses in different taxa is required to bring further insight to this question.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report of activation of a moss (P. patens) SLAC protein by a native SnRK2, albeit weakly, could suggest that the evolution of ABA-SnRK2-SLAC signaling for stomatal closure predates the divergence of ferns (23), and that the absence of native anion channel activation by SnRK2s in C. richardii represents a unique loss, similar to the loss of a stomatal response to blue light in this lineage (24). To address this possibility, we examined the functionality of SnRK2-SLAC combinations in a representative of the lycophyte clade, the earliest diverging clade of vascular plants.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these experiments were performed on herbaceous angiosperms, and there is evidence to suggest that the responses described above differ in both nonherbaceous angiosperms and nonangiosperms Ruszala et al, 2011;McAdam and Brodribb, 2012). These include evolutionary differences in the way stomata perceive signals such as CO 2 , abscisic acid (ABA; Brodribb and McAdam, 2017), leaf-to-air vapor pressure deficit (VPD; McAdam and Brodribb, 2015;Martins et al, 2016), and the intensity and quality of light (Doi et al, 2015). Differences in the stomatal response to these signals will influence the diffusion of CO 2 to mesophyll tissues and, therefore, impact the coordination between A and g s .…”
Section: Mechanisms Of Coordination Between Stomatal Behavior and Mesmentioning
confidence: 99%